Harm Reduction for Adolescents and Young Adults During the COVID-19 Pandemic: A Case Study of Community Care in Reach. (May 2021) - Noyes, Elizabeth; Yeo, Ellis; Yerton, Megan; Plakas, Isabel; Keyes, Susan; Obando, Aura; Gaeta, Jessie M.; Taveras, Elsie M.; Chatterjee, Avik
The coronavirus disease 2019 (COVID-19) pandemic has challenged the ability of harm reduction programs to provide vital services to adolescents, young adults, and people who use drugs, thereby increasing the risk of overdose, infection, withdrawal, and other complications of drug use. To evaluate the effect of the COVID-19 pandemic on harm reduction services for adolescents and young adults in Boston, we conducted a quantitative assessment of the Community Care in Reach (CCIR) youth pilot program to determine gaps in services created by its closure during the peak of the pandemic (March 19–June 21, 2020). We also conducted semistructured interviews with staff members at 6 harm reduction programs in Boston from April 27 through May 4, 2020, to identify gaps in harm reduction services, changes in substance use practices and patterns of engagement with people who use drugs, and how harm reduction programs adapted to pandemic conditions. During the pandemic, harm reduction programs struggled to maintain staffing, supplies, infection control measures, and regular connection with their participants. During the 3-month suspension of CCIR mobile van services, CCIR missed an estimated 363 contacts, 169 units of naloxone distributed, and 402 syringes distributed. Based on our findings, we propose the following recommendations for sustaining harm reduction services during times of crisis: pursuing high-level policy changes to eliminate political barriers to care and fund harm reduction efforts; enabling and empowering harm reduction programs to innovatively and safely distribute vital resources and build community during a crisis; and providing comprehensive support to people to minimize drug-related harms.